The Influence of Masculine Norms and Occupational Factors on Mental Health: Evidence From the Baseline of the Australian Longitudinal Study on Male Health. Issue 4 (July 2018) - Milner, Allison; Kavanagh, Anne; King, Tania; Currier, Dianne
Men employed in male-dominated occupations are at elevated risk of work-related fatalities, injuries, and suicide. Prior research has focused on associations between psychosocial and physical exposures at work and health outcomes. However, masculine norms may also contribute to mental health. We used data from the baseline survey of the Australian Longitudinal Study on Male Health to examine whether: (a) men in male-dominated jobs report greater adherence to masculine norms; (b) being in a male-dominated occupation is associated with poorer mental health; and (c) being in a male-dominated occupation modifies the association between masculine norms and mental health. Masculine norms were measured using the Conformity to Masculine Norms Inventory (CMNI-22). Mental health was assessed using the SF-12. Results of regression analysis (adjusted for covariates) suggest a linear relationship between the extent to which an occupation is male-dominated and endorsement of values on the CMNI-22. Many CMNI-22 subscales were related to poorer mental health. However, the need for self-reliance was identified as the strongest predictor of poorer mental health. The mental health scale did not appear to be patterned by occupational gender composition and we did not find an interaction between the gender ratio of an occupation and the CNMI-22 scale. These findings highlight the need to address harmful aspects of masculinity as a potential cause of mental health problems. More longitudinal research is needed on the social domains in which gender and health are experienced, such as in the workplace.